Two Staining Methods in the Study of Ciliates - Yang, Xianyu; Xin Gao, (IJRDO- Journal of Educational Research, 2019)
Ciliates have two kinds of nuclei, somatic macrocnulei and germinal micronuclei. For the study of nuclear behaviour during their conjugation (sexual reproduction mode), nuclear staining techniques are very important. In the last decade, we studied nuclear behaviour of several species of Paramecium, and several nuclear staining methods were used. Here carbol fuchsin and ‘‘apofluor’’ (a double vital fluorescent dyes of acridine orange and Hoechst 33342) will be introduced.